Excess HPV‐related head and neck cancer in the world trade center health program general responder cohort. Issue 6 (13th February 2019) - Graber, Judith M.; Harris, Gerald; Black, Kathleen; Lucchini, Roberto G.; Giuliano, Anna R.; Dasaro, Christopher R.; Shapiro, Moshe; Steinberg, Michael B.; Crane, Michael A.; Moline, Jacqueline M.; Harrison, Denise J.; Luft, Benjamin J.; et al.
Abstract : The World Trade Center (WTC) attacks exposed rescue and recovery workers to a complex mix of toxicants, including carcinogens. our study compared site‐specific cancer incidence of head and neck cancers (HNC) from 2003 through 2012 among 33, 809 consented WTC General Responder Cohort (GRC) members to the New Jersey State Cancer Registry, using standardized incidence ratios (SIRs). HNC grouped using SEER ICD‐O‐3 codes into HPV‐related (oropharyngeal) and non‐related (other oral‐nasal; laryngeal) tumors based on anatomical site. For the 73 GRC members identified with HNC, proportional hazard regression assessed the relationship between WTC exposure and other socio‐demographic characteristics. An overall excess of HNC was not observed (SIR = 1.00, 95% CI: 0.78, 1.25) but excess cancer was seen in the latest observation period (2009–2012: SIR = 1.4; 95% CI: 1.01, 1.89). A similar temporal pattern was seen for HPV‐related oropharyngeal cancer and laryngeal cancer, but not for non‐HPV‐related sites (oral‐nasal cancer). HNC was significantly associated with increasing age (8% per year, 95% CI: 5%, 12%), non‐Hispanic white ethnic group‐ethnicity (hazard ratio (HR) = 3.51, 95 CI: 1.49, 8.27); there was a borderline association with the 9/11 occupation of military/protective services vs . others (HR = 1.83 95% CI: 0.99, 3.38; p = 0.0504). Caution is needed in interpreting these results given the small number of cases, potential for surveillance bias, and long latency for most cancers. Our findings highlight the need to examine the potentially carcinogenic effects of WTC exposure in the context of other strong risk factors, and the need for continued medical monitoring of WTC responders. Abstract : What's new? Persons involved in rescue, recovery, and clean‐up efforts associated with the September 11, 2001, attacks on the World Trade Center (WTC) in New York City were exposed to numerous toxic chemicals. Within a decade of the attacks, excess cancer incidence was detected among individuals in the WTC Health Program General Responder Cohort (WTCHP GRC). The present report now describes a small but significant increase in head and neck cancer (HNC) in the WTCHP GRC, specifically in human papilloma virus (HPV)‐related oropharyngeal cancer and laryngeal cancer. Whether WTC exposures are associated with increased HPV‐related cancer in WTC responders, however, remains unclear.